Proces przygotowania i wdrażania systemu ocen okresowych pracowników w Bibliotece Uniwersyteckiej w Poznaniu - Małgorzata Dąbrowicz (Biblioteka)
The article outlines the current work on the model framework for designing a local staff evaluation system (SES) and its subsequent implementation at Poznań University Library. The starting point for the preliminary work on the project was setting up objectives of the evaluation, defining the scope, rules and assumptions to be applied in the system. The next stage was to work out and adopt evaluation and assessment criteria and then the choice of methods and tools preparation - evaluation sheets. The planned procedure to be employed by the SES was codified in the written rules to be followed during the implementation. Each stage of the preliminary work involved meetings with staff members of the library where the advances in the system were discussed. Training courses in the system were also provided for would-be evaluators and evaluatees. Further steps in implementing the system are briefly outlined and discussed.